The Price of a Price: On the Crowding out of Social Norms - Maarten C.W. Janssen; Ewa Mendys (Tinbergen Institute, 2001)
There is increasing empirical and experimental evidence thatproviding financial incentives to agents to performcertain socially desirable actions may permanently reduce other typesof motivations to undertake these actions.We study the impact of financial incentives on the desire for socialapproval, using the example of blood donation.We show that in a society with altruists and egoists, who all careabout social approval, introducing a payment intoa voluntary system may actually decrease the amount of blood donated.Withdrawing the financial incentive doesnot restore the norm to donate and may reduce the supply of bloodeven further.
Keywords: I18; D10; Z13; 330; social norms; intrinsic and extrinsic motivation; network effects; health policy; Blutspendedienst; Leistungsmotivation; Leistungsanreiz; Netzwerkökonomik; Gesundheitspolitik; Soziale Norm